Statistical study of polar negative magnetic bays driven by interplanetary fast‐mode shocks. Issue 7 (31st July 2017) - Liou, Kan; Sotirelis, Thomas; Gjerloev, Jesper
Abstract: The question of whether an interplanetary (IP) fast‐mode shock can trigger the substorm expansion is still not resolved. Some scientists believe that the substorm expansion can be triggered by a sudden compression of the magnetosphere if a substorm growth phase is in progress (e.g., the magnetosphere precondition hypothesis). Such a hypothesis has not been rigorously tested. Here we study 258 positive sudden impulse (SI + ) events associated with interplanetary fast‐mode shocks observed by the ACE spacecraft from 1998 to 2009. The westward auroral electrojet SML index, derived from the SuperMAG network geomagnetic field data, is used to check for negative magnetic bays. It is found that the probability of having a magnetic bay onset that follows a shock impact peaks (~27%) sharply and immediately (within 3 min) after the shock‐induced SI + . This indicates that the majority of the shock events do not lead to magnetic bays. A superposed epoch analysis of the shock events associated with (Type‐Y) and without (Type‐N) negative bays indicates that the Type‐Y events had stronger (~40%) solar wind driving than the Type‐N ones. This result generally supports the magnetosphere precondition hypothesis. We also found that (1) Type‐Y events are associated with even stronger (~56%) solar wind driving downstream of the shock than Type‐N events and (2) there is a good correlation between the SML and the polar cap magnetic PC indices both upstream and downstream of the shock. It is suggested that sharp decreases in SML immediately after a shock impact are not associated with the substorm‐driven DP ‐1 current system but with the convection‐driven DP ‐2 current system. Key Points: Most of interplanetary shocks do not lead to polar magnetic bays For those that do, they are associated with stronger shocks and larger dayside merging rate Shock‐associated magnetic bays are associated with DP ‐2 currents